Optic nerve head factors associated with initial central visual field defect in primary open-angle glaucoma - Eunoo Bak; Martha Kim; Seok Hwan Kim; Kyoung Min Lee (Scientific Reports, 2024)
Abstract We investigated optic nerve head factors associated with initial parafoveal scotoma (IPFS) in primary open-angle glaucoma. Eighty (80) patients with an IPFS and 84 patients with an initial nasal step (INS) were compared. Central retinal vascular trunk (CRVT) deviation from the Bruch’s membrane opening (BMO) center was measured as a surrogate of lamina cribrosa (LC)/BMO offset, and its obliqueness was defined as the absolute value of angular deviation from the fovea-BMO axis. Proximity of retinal nerve fiber layer defect (RNFLD) was defined as the angular deviation of the inner RNFLD margin from the fovea-BMO axis. Microvasculature dropout (MvD) was defined as a focal sectoral capillary dropout with no visible microvascular network identified in the choroidal layer. Factors associated with IPFS, as compared with INS, were assessed using logistic regression analyses and conditional inference tree analysis. The IPFS group had more oblique CRVT offset (P < 0.001), RNFLD closer to the fovea (P < 0.001), more MvD (P < 0.001), and more LC defects (P < 0.001) compared to the INS group. In logistic regression analyses, obliqueness of CRVT offset (P = 0.002), RNFLD proximity (P < 0.001), and MvD (P = 0.001) were significant factors influencing the presence of IPFS. Conditional inference tree analysis showed that RNFLD closer to the fovea (P < 0.001) in the upper level, more oblique CRVT offset (P = 0.013) and presence of MvD (P = 0.001) in the lower level were associated with the probability of having IPFS. IPFS was associated with closer RNFLD location to the fovea when assessed from the BMO. Oblique LC/BMO offset may not only mask RNFLD proximity to the fovea due to a deviated funduscopic disc appearance, but also potentiate IPFS via focal LC defect and MvD.